A New Hole Transport Material for Efficient Perovskite Solar Cells With Reduced Device Cost (Solar RRL 1∕2018). Issue 1 (15th January 2018) - Sun, Yuhao; Wang, Changlei; Zhao, Dewei; Yu, Jiangsheng; Yin, Xinxing; Grice, Corey R.; Awni, Rasha A.; Shrestha, Niraj; Yu, Yue; Guan, Lei; Ellingson, Randy J.; Tang, Weihua; et al.
Abstract : A new and low‐cost hole selective material, 2, 6, 14‐tris(5'‐(N, N‐bis(4‐methoxyphenyl) aminophenol‐4‐yl)‐3, 4‐ethylenedioxythiophen‐2‐yl)‐triptycene, i.e. TET, for efficient perovskite solar cells (PVSCs) has been synthesized and demonstrated in article No.1700175 . As a 2, 2', 7, 7'‐Tetrakis(N, N'‐di‐p‐methoxyphenylamine)‐9, 9'‐ spirobifluorene (spiro‐OMeTAD) derivative, TET inherits excellent optoelectronic properties and overcomes the major shortfalls of spiro‐OMeTAD. Planar PVSCs with TET hole selective layers (HSLs) have achieved a maximum power conversion efficiency (PCE) of 19.1% under reverse voltage scan and steady‐state efficiency of 18.6%, comparable with those (19.5% PCE and 19.0% steady‐state efficiency) of PVSCs using spiro‐OMeTAD HSLs. Importantly, these efficient PVSCs used very thin TET HSLs (about 30 nm) without the need of oxygen doping. Considering the lower lab synthesis and purification cost ($123/g vs $500/g) and thinner HSL (30 nm vs 200 nm), the cost for TET on a unit area of one device is significantly lower (25 times) than that for high‐purity spiro‐OMeTAD.